An estimation of efficiency and effectiveness of international commercial arbitration as applied to the Philippine Dispute Resolution Center, Inc. - Borra, Katrina Pelayo (Animo Repository, 2007)
Globalization today has increased the number of international commercial transactions occurring all over the world. This increase in transactions has also resulted to an increase in international commercial disputes. Parties, however, seek a neutral venue in resolving international commercial disputes. Usually, when disputes are litigated in domestic courts, culture, nationality, conflicts of law and other biases are factored in the consideration of the judgment. With a neutral venue, parties are assured of an impartial judgment. This is the reason parties resort to arbitration. Two primary reasons for entering into arbitration are promptness of resolution and cost-effectiveness. Unlike litigation, arbitration is considered to be less expensive and time-consuming. Arbitration is also the only form of extrajudicial dispute resolution that has binding effect, which can be confirmed and enforced in courts all over the world, especially in those countries which have ratified the New York Convention. Many venues exist for international commercial arbitration. The world’s leading international commercial arbitration center is the International Chamber of Commerce’s International Court of Arbitration (ICA). In the Philippines, the Philippine Dispute Resolution Center, Inc. (PDRCI) provides both domestic and international arbitration services. ii This paper estimates the efficiency of services in PDRCI and effectiveness of arbitration in the Philippines. Procedural efficiency of PDRCI is measured by means of speed of disposition and costs of arbitration. Effectiveness, in this study, is determined by virtue of success rate of arbitral awards’ enforcement in the Philippines. As a result, this study shows that ratio of domestic to international cases handled by PDRCI is 10 to 1. On average, international cases are disposed faster (11 months) than domestic cases (15.5 months). The best practice in promptness in resolution can be observed in the international case, where complaint to arbitrator-appointment is 3 months, and arbitrator-appointment to award is 7 months. The fastest disposition of an arbitration case is therefore 10 months. Parties can also expect an arbitration case in PDRCI to last 13.25 months, with an average of 4.75 months spent on the stage of complaint to arbitrator-appointment, and 8.5 months on arbitrator-appointment to award, regardless of the nature of the case, whether domestic or international. It has also been observed that percentage costs are inversely related to Amount in Dispute (AID). Thus, the higher the AID, the lower the proportional costs and the lower the AID, the higher the proportional costs. The range of Cost / AID is from 1.39% to 4.47%. On average, parties can expect to spend 2.96% of the AID for administrator and arbitrator’s fees in the PDRCI-administered arbitration case. In terms of effectiveness, majority of Supreme Court decisions confirm arbitral awards. In international cases, 100% of the Supreme Court relating to enforcement of iii foreign arbitral awards from 1901 to 2000 were confirmed. For domestic arbitral awards, seventy-two (72%) were confirmed, while eleven percent (11%) were vacated and seventeen percent (17%) modified. For the modified domestic arbitral awards, 100% of these cases were modified on the ground of evident miscalculation in figures. For the vacated domestic arbitral award, all these cases were vacated on the ground of grave abuse of discretion. Recommendations were also provided by the researcher, which include: 1) the modification of the performance measurement framework to include other measurable and non-measurable key performance indicators of efficiency and effectiveness of international commercial arbitration; 2) benchmarking of ICA, SIAC and NLRC for comparative analysis of its data with PDRCI; 3) performance measurement comparison of arbitration and litigation in the Philippines; and, 4) monitoring system for PDRCI to evaluate periodically the effectiveness and efficiency of its performance as an arbitral institution.